2008
DOI: 10.1016/j.pain.2008.01.018
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mood on pain responses and pain tolerance: An experimental study in chronic back pain patients

Abstract: Although chronic pain and depression commonly co-occur, causal relationships have yet to be established. A reciprocal relationship, with depression increasing pain and vice versa, is most frequently suggested, but experimental evidence is needed to validate such a view. The most straightforward approach would be a demonstration that increasing or decreasing depressed mood predictably modifies pain responses. The current experiment tested whether experimentally induced depressed and happy mood have differential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
102
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(114 citation statements)
references
References 40 publications
10
102
1
1
Order By: Relevance
“…happy music; Tang et al, 2008;van Laarhoven et al, 2012). Since participants liked all music in this study, it is possible that some emotional transference existed between relaxing and happy music, with the relaxing music inducing positive emotions in addition to unique feelings of relaxation (Tang et al, 2008). However, it could be argued that the different findings between happy and relaxing music could be a results of a time perception mechanism: participants perceived time passing differently when listening to happy and relaxing music.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…happy music; Tang et al, 2008;van Laarhoven et al, 2012). Since participants liked all music in this study, it is possible that some emotional transference existed between relaxing and happy music, with the relaxing music inducing positive emotions in addition to unique feelings of relaxation (Tang et al, 2008). However, it could be argued that the different findings between happy and relaxing music could be a results of a time perception mechanism: participants perceived time passing differently when listening to happy and relaxing music.…”
Section: Discussionmentioning
confidence: 99%
“…Tang et al (2008) found that a negative mood state increased self-reported pain intensity and decreased pain tolerance, while a positive mood reduced self-reported pain intensity and increased pain tolerance.…”
mentioning
confidence: 95%
“…Some data suggest that depression may lower physical pain tolerance (Chiu et al, 2005;Tang et al, 2008). Indeed, associations between depression and pain have been identified in people who suffer from chronic pain disorders, such as fibromyalgia or neuropathic pain (Maletic & Raison, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, to understand better how chronic pain can be reduced and better tolerated, is of relevance. 9 Regarding validity of DAPOS, the results can be generalized to other patients in clinical settings.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 In contrast, the hypothesis that happy mood, that is positive affect, can significantly reduce pain perception and increases pain tolerance has been demonstrated and it may certainly contribute in the management of chronic musculoskeletal pain. 9,10 Researchers and clinicians evaluating mood have a variety of options. 11 Most of the questionnaires used to assess depression and anxiety have been shortened to make them more user friendly but still, showing reliability and validity consistent with the original versions.…”
mentioning
confidence: 99%